Catalonia and the mobilization of military resources for the expedition to Sicily, 1718 - Martí Fraga, Eduard (Cuadernos de Historia Moderna, 2019)
A recurring theme of Catalan historiography is the debate on the effects of Philip V’s military policy on the economy of Catalonia after 1714. This question, however, is part of a broader debate: assess the ways in which the Crown got mobilizes their military resources, who benefited from it and what effects it had on the territory. In the end, it is about analyzing the ways in which the Bourbon state was configured. From the analysis of the mobilization of military resources for the expedition of the conquest of Sicily in 1718, this article aims to answer some of these questions.
Keywords: Sicily expedition; Contractor State; micro-contract; entrepreneurs; Catalonia